Oestrus characteristics in Jakhrana goats - GOEL, A K; AGRAWAL, K P (The Indian Journal of Animal Reproduction, 2023)
Study on oestrus characteristics ( oestrus symptoms and duration) at different physiological stageswas conducted in two hundred eighty two (pubertal: 90. post-pubertal: 20, and post-partum: 172) Jakhrana goats,maintained under semi-intensive system of management at experimental sheds of this institute. Oestrus detectionwas carried out at 6-12 hours interval. Behavioural oestrus symptoms (moderate) were observed at puberty whilegoats at first post-partum oestrus expressed behavioural oestrus of weak intensity. Post-pubertal (nulliparousand parous) goats exhibite~ typical oestrus symptoms. Oestrus duration in pubertal goats averaged 27.97± 1.43hr (range: 12 to 60 hr) and majority of goats remained in oestrus for 24 to 36 hr. Type and season of birth did notinfluence its duration (P>0.05). In post-pubertal goats oestrus duration averaged 29.28±0.98 hr (nulliparous:28.448 hr) oestruses was also noticed. In post-partum goats, first oestrusaveraged 25.25±0.88 hr(range: 12 to 60 hr) and majority (64%) of goats remained in oestrus for 24 to 36 hr. Goatskidded during Dec.-Jan. had highest (28.50± 1.77 hr) and those kidded during April had lowest (17.14±2.42 hr)post-partum oestrus duration (P0.05) and majority of them remained in oestrus for 24 to 36 hr. Infonnation onoestrus symptoms and duration will help to mate Jakharana goats at proper time for optimum flock fertility.
Keywords: Oestrus symptoms; duration; physiological stages; Jakhrana goat